Shaddock peel derived nitrogen and phosphorus dual-doped hierarchical porous carbons as high-performance catalysts for oxygen reduction reaction. (11th October 2019) - Lu, Lei; Yu, Jia; Wu, Zongdeng; Fan, Jiawei; Lei, Wu; Ouyang, Yu; Xia, Xifeng; He, Guangyu; Hao, Qingli
Abstract: Oxygen reduction reaction (ORR) plays a key role in the application of fuel cells. Here, we used shaddock peel to fabricate a set of N, P dual-doped hierarchical porous carbons, abbreviated as NPSPs, where the carbons were carbonized, activated and dual-doped via a simple one-step pyrolyzation. Contrast results indicate the contents of pyridinic-N, graphitic-N and P–C species increase with the rising of temperatures, and the temperature also affects the degree of graphitization, surface area, morphology, thus influences the ORR performance. More importantly, the NPSP-900 demonstrates an outstanding ORR activity with a comparable half-wave potential (0.83 V vs. RHE) and higher current density with respect to commercial Pt/C, following 4e transfer pathway. Our work illustrates that NPSP-900 is a promising cathode for fuel cells because of its simple preparation, waste utilization, excellent ORR performance, good methanol tolerance and superior stability. Graphical abstract: Image 1 Highlights: One-step pyrolysis can accomplish carbonization, activation and N, P-dual doping. NPSPs own hierarchical porous structures with high BET surface areas. Higher temperature can enhance ORR activities with improved doping N/P species. NPSP-900 owns a close ORR activity compared with Pt/C, following 4e transfer way. NPSP-900 shows a remarkable methanol tolerance and superior stability.